Next generation sequencing identifies a novel variant in the NR5A1 gene in a 46,XY female with complete gonadal dysgenesis - Gunbey, Omer; Esen, Ihsan; Paksoy, Firdevs D.; Okdemir, Deniz (Galenos Publ House, 2025)
To report a novel variant in the NR5A1 gene as a cause of 46,XY complete gonadal dysgenesis (Swyer syndrome). A 12.5-year-old prepubertal girl presented with the complaint of short stature and was evaluated in our clinic after pelvic ultrasonography revealed an absent uterus and ovaries. In pubertal examination, she was at Tanner stage I, had a fully female phenotype, and no clitoromegaly. Gonads were not palpable on examination. Laboratory investigations, including hemogram and biochemical tests, were normal. Celiac antibodies were negative, and thyroid function tests were within normal limits. Patient's serum LH level was 11.7 mIU/mL, FSH 81.3 mIU/mL, estradiol <15 pg/mL, total testosterone <7.0 ng/dL, DHEA-S 64.4 mu g/dL, ACTH 18.1 pg/mL, and cortisol 13.4 mu g/dL. Magnetic resonance imaging revealed a hypoplastic uterus in a band-like shape, with no visible ovaries. No appearance consistent with testicular tissue was identified. Karyotype analysis revealed a 46,XY pattern. Estrogen therapy was initiated for the patient. No pathogenic variant was detected in the SRY gene analysis. As part of the molecular analysis using the next-generation sequencing (NGS) method, a heterozygous p.V15L (c.43G>T) variant was detected in the NR5A1 gene (NM_004959.5). A total of 26 genes were screened as part of this panel, including DHX37, SRY, WT1, DHH, ZFPM2, PPP1R12A, NR5A1, GTF2H5, MAP3K1, HSD17B4, SOX9, DMRT3, NR0B1, and GATA4. In summary, this case report describes a novel heterozygous NR5A1 variant identified in an adolescent with 46,XY complete gonadal dysgenesis (Swyer syndrome).
Keywords: 46; XY complete gonadal dysgenesis; Swyer syndrome